Sifat Fisik dan Mekanik Batang Gewang (Corypha utan Lamk.) dari Nusa Tenggara Timur Physical and Mechanical Properties of Gewang (Corypha utan Lamk.) Stem from East Nusa Tenggara - Kurnia Wiji Prasetyo; Subyakto Subyakto; B. Paul Naiola (Jurnal Ilmu dan Teknologi Kayu Tropis, 2008)
Gewang (Corypha utan Lamk.) is an important palm grown wild in the savannah of East Nusa Tenggara, Indonesia. The genus Corypha, belong to Arecaceae or Palmae consist of about 8 species distributed from tropical Africa to India, tropical Asia, Indochina, Malaysia, and Quensland. Corypha grows in lowland of very dried climate and savannah. The local people have used this palm traditionally for many purposes to fulfill their daily needs. Trunks are used for producing starch for food, cattle food (putak), building material for housing, furniture and fence.Basic properties of stem from Gewang palm are identified according to the height and depth of samples in the stem. The properties identified are physical properties including density, water absorbtion and shrinkage on thickness and length direction; mechanical properties including modulus of elasticity (MOE), modulus of rupture (MOR) and maximum crushing strength pararel to grain.Almost all properties tested are affected significantly by the height and depth of samples in the Gewang stem, where the influence of depth stem factor is higher than the height stem factor. Gewang stem from the bottom part of the stem produces better properties than middle and top part, indicates by a higher density, lower water absorption and shrinkage values. Similarly, physical properties of the outer part Gewang stem is higher than those in the medium and center parts. The mechanical properties result shown same phenomena that the bottom part of Gewang stem produces better properties than middle and top part, indicates by a higher modulus of elasticity, modulus of rupture and maximum crushing strength pararel to grain values. Similarly, mechanical properties of the outer part Gewang stem is higher than those in the medium and center parts.